1993
DOI: 10.1254/jjp.61.13
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective Action of L-Arginine against HCl-Induced Gastric Injury in Rats: Involvement of Nitric Oxide?

Abstract: ABSTRACT-We examined the cytoprotective effect of L-arginine on gastric damage induced by 0.6 N HC1 in rats and investigated whether the mechanism of this action is related to the nitric oxide (NO)-mediated protection. The animals were given 0.6 N HCI by gavage and killed 1 hr later. L-Arginine (100, 300 and 750 mg/kg) given p.o. 30 min before HC1 treatment prevented these lesions in a dose-dependent manner, but had no effect when given i.v. (200 mg/kg). Similar effects were observed by D-arginine but not by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…The increase of GMBF by ASA has been also reported in rats subjecting to cold exposure, despite potentiating the ulcerogenic response in the stomach [22]. In the present study, we also confirmed our previous observation that L-NAME did not reduce but caused a temporal increase of GMBF under urethane anesthetized conditions [23]. Tepperman and Whittle [24] reported significant decrease of GMBF after administration of L-NAME in pentobarbital-anesthetized rats, while Lippe and Holzer [25] reported that inhibition of NO synthesis failed to alter basal GMBF in the rats anesthetized with urethane.…”
Section: Discussionsupporting
confidence: 93%
“…The increase of GMBF by ASA has been also reported in rats subjecting to cold exposure, despite potentiating the ulcerogenic response in the stomach [22]. In the present study, we also confirmed our previous observation that L-NAME did not reduce but caused a temporal increase of GMBF under urethane anesthetized conditions [23]. Tepperman and Whittle [24] reported significant decrease of GMBF after administration of L-NAME in pentobarbital-anesthetized rats, while Lippe and Holzer [25] reported that inhibition of NO synthesis failed to alter basal GMBF in the rats anesthetized with urethane.…”
Section: Discussionsupporting
confidence: 93%
“…The protective action of L-arginine against chronic gastric ulcer in rats appears to involve gastric hyperemia mediated by NO, and the ulcer healing properties of L-arginine may depend upon its hyperemic and angiogenic actions, possibly involving NO (Brzozowski et al, 1997). On the other hand, the cytoprotective effect 330 TODA AND HERMAN of L-arginine against HCl-induced gastric injury in rats invokes endogenous prostaglandins rather than NO (Takeuchi et al, 1993). Copious diarrhea produced following the oral administration of castor oil to rats was inhibited or prevented by L-NMMA or L-NAME by decreasing the intestinal fluid accumulation and Na ϩ secretion, suggesting that endogenous NO participates in castor oil-induced diarrhea (Mascolo et al, 1993).…”
Section: Pathological Implicationsmentioning
confidence: 99%
“…26) It has been reported that an increase in gastric mucosal blood flow is observed after treatment with mild irritants 32) and that inhibition of the increase in mucosal blood flow by indomethacin, N G -nitro-L-arginine methyl ester (L-NAME), or sensory ablation, aggravates mucosal lesions resulting from strong irritants. [32][33][34] Based on such evidence, the mucosal microcirculation is believed to play an important role in mucosal protection by removing back-diffused acid in the mucosa and transporting humoral factors involved in cytoprotection into the epithelial cells. It has been suggested that gastric motility changes play a role in the development and prevention of gastric lesions following both stress and administration of nonsteroidal anti-inflammatory drugs.…”
Section: -4 the Mechanism Of Cytoprotectionmentioning
confidence: 99%